PENERAPAN STRATEGI GUIDED NOTE TAKING DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS IV SDN TLEPOKWETAN - NURVICTASARI, PRANITA (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Pranita Nurvictasari1, Tri Saptuti Susiani2, Joharman3 FKIP, PGSD Universitas Sebelas Maret e-mail: nyieth_4nt0@yahoo.co.id 1. Mahasiswa PGSD FKIP UNS 2,3. Dosen PGSD FKIP UNS Abstract: Implementation of Guided Note Taking Strategy in Improving Social Studies Learning 4th Grade student at Tlepokwetan Elementary School. The purpose of this research is to describe the step implementation of Guided Note Taking strategy in improving Social studies learning fourth grade students in elementary school. This research uses classroom actions research methods are carried out in the three cycles. Each cycle consists of two meeting and each meeting consists of planning, action, observation, and reflection. The data sources of this research is the fourth grade students of elementary school. Data collecting methods are collected through observation, interview, test and documentation. The validity of data using the triangulation source. The data analysis is used by this research is quantitatif and qualitatif data analysis. The result showed that implementation of Guided Note Taking strategy can improve learning about Social Studies. Process the study mount equal to 44,61% from cycle I until cycle III, while result learn to experience of the improvement 75,00% from pretes 12,50%. Keywords: Guided Note Taking strategy, Improved Learning, Social studies Abstrak: Penerapan Strategi Guided Note Taking dalam Peningkatan Pembelajaran IPS Siswa Kelas IV SDN Tlepokwetan. Penelitian ini bertujuan untuk mendeskripsikan langkah penerapan strategi Guided Note Taking dalam peningkatan pembelajaran IPS. Penelitian ini menggunakan metode penelitian tindakan kelas yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari 2 pertemuan dan setiap pertemuan dilaksanakan melalui tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV SD. Teknik pengumpulan data menggunakan observasi, wawancara, tes dan dokumentasi. Validasi data menggunakan teknik triangulasi sumber. Analisis data yang digunakan dalam penelitian ini adalah analisis data kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa langkah penerapan strategi Guided Note Taking yang tepat dapat meningkatkan pembelajaran IPS. Proses pembelajaran meningkat sebesar 44,61% dari siklus I sampai siklus III, sedangkan hasil belajar mengalami peningkatan 75,00% dari pretes 12,50%. Kata kunci: Strategi Guided Note Taking, Peningkatan Pembelajaran, IPS